Differentiation of Rat Adipose-Derived Stem Cells into Parathyroid-Like Cells - Ping Zhang; Hao Zhang; Wenwu Dong; Zhihong Wang; Yuan Qin; Changhao Wu; Qi Dong (International Journal of Endocrinology)
Background. The current treatment for postoperative hypoparathyroidism has shortcomings, such as repeated blood monitoring for dosage adjustment, uncertain long-term efficacy, and the high price of recombinant parathyroid hormone therapy. Adipose-derived stem cells can undergo adipogenic and osteogenic differentiation in vitro and are considered a novel source of parathyroid-like cells, but the idea lacks theoretical basis and feasibility. We aimed at establishing a protocol for differentiating adipose-derived stem cells into parathyroid-like cells for treating hypoparathyroidism. Materials/Methods. Adipose-derived stem cells were isolated and purified from the inguinal adipose tissue of Sprague Dawley rats. Adipogenic differentiation and osteogenic differentiation of the cells were identified by oil red O and alizarin red S staining, respectively. The adipose-derived stem cells were stimulated by sonic hedgehog (SHH) and activin A. The differentiation of the adipose-derived stem cells to parathyroid-like cells was confirmed by the detection of parathyroid hormone and the related parathyroid markers. Results. Adipose-derived stem cells were successfully isolated and purified from the rat adipocytes. The adipogenic and osteogenic differentiation capabilities of the adipose-derived stem cells were determined. SHH and activin A stimulated parathyroid hormone secretion by the adipose-derived stem cells and significantly increased the expression of calcium-sensing receptor (CaSR), parathyroid hormone, and glial cells missing homolog 2 (GCM2) in the cells in a time- and concentration-dependent manner. Conclusion. We successfully differentiated rat adipose-derived stem cells into parathyroid-like cells, which will pave a new route to curing hypoparathyroidism.